PROTOTYPE PENGUKURAN TINGGI DEBIT AIR PADA BENDUNG DENGAN MENGGUNAKAN SENSOR ULTRASONIK BERBASIS ARDUINO MEGA 2560 - Jawas, Hilmy; Wirastuti, N.M.A.E.D.; Setiawan, Widyadi (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUM, 2018)
Prototype system for measuring the level of water debit on weir by using an Arduino mega 2560 based ultrasonic sensor. It is created for detecting flood system that works automatically by finding out the water level on the weir’s surface. This water surface level monitoring system is conducted by implementing an Arduino mega 2560 based ultrasonic system, which will compute the water level created at certain levels. This prototype device for measuring the water level on weir by using Arduino mega 2560 based ultrasonic sensor consists of Arduino Mega 2560, HC-SR04 Ultrasonic Sensor, 16 X 2 LCD, and Buzzer. Arduino serves to determine the sensor value and provides the output accordingly with the sensor measurement. HC-SR04 Sensor functions to read the water level from a distance of 2 cm to 300 cm, this water level would be displayed on the LCD and the sound from Buzzer is going to sound the alarm at an altitude of 16 cm to 45 cm.